ByzRev 07.2025.054: John C. Davis – Martin Hinterberger, The Metaphrase of Niketas Choniates’ History: (Byzantinisches Archiv 45). Berlin – Boston: De Gruyter 2025. - Wahlgren, Staffan (The Byzantine Review, 2025)
John C. Davis – Martin Hinterberger, The Metaphrase of Niketas Choniates’ History (Byzantinisches Archiv 45). Berlin – Boston: De Gruyter 2025. lxiv+743 pp. – ISBN 978-1-61451-596-8; e-ISBN (PDF) 978-1-61451-448-0